Ответы и объяснения

2013-07-07T19:04:40+00:00

х-√(2-х)=-10

sqrt(2-x)=x+10

Возводим в квадрат, при этом x+10>0; x>-10 

2-x=(x+10)^2

2-x=x^2+100+20x

x^2+100+20x-2+x=0

x^2+21x+98=0

D=441-398=49

x1=(-21+7)/2=-7; x2=(-21-7)/2=-14

Учитывая ОДЗ,

ответ: х=-7

Лучший Ответ!
2013-07-07T19:21:14+00:00

x - √(2 - x) = -10

-√(2 - x) = -10 - x | × (-1)

√(2 - x) = 10 + x

 

(√(2 - x))² = (10 + x)²

 

ОДЗ: 

 

x + 10 > 0

x > -10

 

2 - x = 10² + 2 × 10 × x + x²

2 - x = 100 + 20x + x²

x² + 20x + 100 = 2 - x

x² + 20x + 100 - 2 + x = 0

 

x² + 21x + 98 = 0

 

D = b² - 4ac = 21² - 4 × 1 × 98 = 441 - 392 = 49

 

x₁,₂ = (-b ± √D) ÷ 2a

 

x₁ = (-21 + √49) ÷ 2 = (-21 + 7) ÷ 2 = - 14 /2 = -7

x₂ = (-21 - √49) ÷ 2 = (-21 - 7) ÷ 2 = -28 /2 = -14

 

-7 > -10

-14 < -10

 

Ответ: -7.